Ocular Surface Manifestations of Ophthalmia Nodosa from Caterpillar Setae - Karlo Marco Claudio; Ulysses Joseph L. Yap, MD-MBA (Philippine Journal of Ophthalmology)
Objective: To report three consecutive cases of ophthalmia nodosa due to caterpillar hair (setae).